Bullying Behavior in School Reviewed from Forgiveness and Peer Social Support - Febe Eunike Panyuwa; Augustina Sulastri (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Bullying is an important issue in the Indonesian education system, so efforts are needed to identify the causes. This study aimed to analyse the relationship between forgiveness and peer support with bullying behaviour at school. The research hypothesis is that there is a relationship between forgiveness and peer support with bullying behaviour at school; a negative relationship between forgiveness and bullying behaviour at school; and a negative relationship between peer support and bullying behaviour at school. The study used a quantitative correlational approach and involved 102 high school students from Eastern Indonesia who had experienced bullying at school. Data were obtained using a scale distributed online. Data analysis used multiple regression analysis. The results of this study showed a significant relationship between forgiveness and peer support with bullying behaviour at school (F (2, 99) = [9.813], p = 0.001). Schools, parents and students need to understand forgiveness and the role of peers in preventing bullying behaviour.